Contextual Valence and Sociality Jointly Influence the Early and Later Stages of Neutral Face Processing - Xu, Mengsi (Front Psychol, 2016)
Recent studies have demonstrated that face perception is influenced by emotional contextual information. However, because facial expressions are routinely decoded and understood during social communication, sociality should also be considered—that is, it seems necessary to explore whether emotional contextual effects are influenced by the sociality of contextual information. Furthermore, although one behavioral study has explored the effects of context on selective attention to faces, the exact underlying mechanisms remain unknown. Therefore, the current study investigated how valence and sociality of contextual information influenced the early and later stages of neutral face processing. We first employed an established affective learning procedure, wherein neutral faces were paired with verbal information that differed in valence (negative, neutral) and sociality (social, non-social), to manipulate contextual information. Then, to explore the effects of context on face perception, participants performed a face perception task, while the N170, early posterior negativity (EPN), and late positive potential (LPP) components were measured. Finally, to explore the effects of context on selective attention, participants performed a dot probe task while the N2pc was recorded. The results showed that, in the face perception task, faces paired with negative social information elicited greater EPN and LPP than did faces paired with neutral social information; no differences existed between faces paired with negative and neutral non-social information. In the dot probe task, faces paired with negative social information elicited a more negative N2pc amplitude (indicating attentional bias) than did faces paired with neutral social information; the N2pc did not differ between faces paired with negative and neutral non-social information. Together, these results suggest that contextual information influenced both face perception and selective attention, and these context effects were governed by the interaction between valence and sociality of contextual information.